Software for the self technology and culture - Smith, Anthony (Oxford Univ. Press, 1996)
Smith sees entertainment itself becoming more central to culture and society because people will have increasingly more leisure time. Although hightech advances have been made in the world of information exchange, science, commerce, industry, and defense. Smith believes entertainment is crucial to the forms that new technology will take and the uses to which they will be put. As Smith pointedly says, "the entertainment industry, alongside the health industry, is as close as any other to the things that people actually want and are willing to pay for.
Keywords: Gesellschaft; Massenmedien; Information technology -- Social aspects; Mass media -- Social aspects; Sozialer Wandel; Informationstechnik; Software; Kultur